Ibanag reduplication patterns as signals of meaning - a descriptive analysis - Manaligod, Araceli (Mia) 1935- (s.n.], 1969)
This study was used as a springboard for a formal contrastive analysis of Ibanag and Tagalog. Interviews of native speakers and recognized authorities on the language were conducted, along with a descriptive analysis. It was found that there are 12 meanings signalled by the reduplication patterns and that in the process of reduplication, some morphonemic changes occur.